Floating photocatalyst based on Fe doped TiO2 immobilized on vermiculite for degradation of ciprofloxacine - Nguyen Thi Hue,; Chu Viet Hai,; Vu Van Tu,; Nguyen Xuan Dat,; Luu Van Huyen,; Nguyen Manh Nghia, (Vietnam Journal of Science and Technology, 2025)
In this work, a floating photocatalyst based on Fe doped TiO2 immobilized vermiculite is synthesised via sol gel process. The samples was characterized with X-ray diffraction, N2 isothermal loops, scanning electron microscopy, high-resolution transmission electron microscopy, and ultraviolet – visible absorption to find its crystal phase composition, particle size, porosity, morphology,  and light absorption ability, respectively. The porosity of the support was enhanced as the natural vermiculite was pretreated by acid HNO3 40% to increases its specific surface area strongly from 6 to 323 m2/g. Crystalline anatase TiO2 was combined with vermiculite support to form a floating photocatalyst. The enhanced visible light absorption was achieved by adding 0.6 % mol Fe dopant in TiO2 structure. The total adsorption and photocatalytic efficiency in ciprofloxacine degradation of Fe doped TiO2 immobilized vermiculite was approximately 60 % while that of pure TiO2 immobilized vermiculite was only about 40 %. This result showed the improvement of floating photocatalysts in degrading antibiotics in water using visible light